Pelatihan Desain Grafis Menggunakan Aplikasi Canva Untuk Siswa Di SMK Kesehatan Binatama - Abd Mizwar A. Rahim; Theopilus Bayu Sasongko; Hannan Asrawi (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Technological development is an important factor as a driver of growth and progress in a country. Technology today plays a very important role, especially in the field of education. One way to deal with this is utilizing technology, which can be done by starting to introduce technology to students at an early age through graphic design using the Canva app. In the environment of SMK Kesehatan Binatama, the use of technology in teaching activities has not been done effectively. Learning activities are still done normally without frequently using technology, so it is necessary to have Canva training as a form of technology adaptation and a means to channel the creativity of the students. The methods used are training methods that include material delivery, practice, and evaluation. Training activities run smoothly: each student can follow a whole range of activities from start to finish, and each student may create one graphic design independently.